Integration of Resource-Based View, Dynamic Capabilities Theory, and Social Cognitive Theory in Improving Organizational Performance through Human Capital Readiness in the Digital Transformation Era - Moektiwibowo, Hari; Hendayana, Yayan (Dinasti Publisher, 2025)
Digital transformation has fundamentally changed the way employees are managed and how companies strategize. In Indonesia, particularly among small and medium-sized enterprises (SMEs), the level of readiness to utilize technology remains low due to limited financial resources, a limited understanding of digital technologies, and restricted access to technology facilities. This study seeks to combine three main theories: “Resource-Based View (RBV), Dynamic Capabilities Theory (DCT), and Social Cognitive Theory (SCT)” to explain the role of HR readiness in improving company performance in the digital era. This study employs the Systematic Literature Review (SLR) method, collecting articles from sources such as Scopus, Emerald Insight, and SpringerLink, spanning the years 2019 to 2025. The results indicate that HR readiness acts as a bridge between strategic resources, the company's adaptive capabilities, and social learning behaviors. The combination of dynamic capabilities, digital leadership, and self-confidence in the face of digital change provides a sustainable competitive advantage. This study concludes that to succeed in digital transformation, companies must implement a human-centered approach that integrates strategy, technology, and human resource development.